2007
DOI: 10.2144/000112528
|View full text |Cite
|
Sign up to set email alerts
|

Serum albumin leads to false-positive results in the XTT and the MTT assay

Abstract: Tetrazolium salts like 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) or sodium 2,3-bis-(2-methoxy-4-nitro-5-sulfophenyl)-2H-tetrazolium-5-carboxanilide (XTT) that form formazans after reduction are widely used to investigate cell viability. Besides cellular enzymes, some constituents of cell media and other substances reduce tetrazolium salts, thereby interfering with these assays. We describe here that different preparations of serum albumin from bovine or human origin can lead to a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 11 publications
1
33
0
Order By: Relevance
“…Glycolysis played an important role in MTT reduction by astroglia, whereas mitochondrial oxidative metabolism -in neurons (Takahash i et al, 2002) Growth state The growth state of cells, exponential or confluent, has moderate but significant influence on MTT reduction (Liu and Dalgleish, 2009) Serum albumin In a concentration-dependent manner, human and bovine albumins increased formazan formation via direct chemical interaction with MTT or XTT. Free SH-groups of cysteine residues were implicated (Funk et al, 2007) Cholesterol Cholesterol/methyl-β-cyclodextrin complex decreased MTT reduction, enhanced exocytosis of formazan, and promoted cell type-dependent increase in oxygen consumption. No cytotoxicity of cholesterol itself was revealed in trypan blue and propidium iodide assays.…”
Section: Conditioned Mediummentioning
confidence: 99%
“…Glycolysis played an important role in MTT reduction by astroglia, whereas mitochondrial oxidative metabolism -in neurons (Takahash i et al, 2002) Growth state The growth state of cells, exponential or confluent, has moderate but significant influence on MTT reduction (Liu and Dalgleish, 2009) Serum albumin In a concentration-dependent manner, human and bovine albumins increased formazan formation via direct chemical interaction with MTT or XTT. Free SH-groups of cysteine residues were implicated (Funk et al, 2007) Cholesterol Cholesterol/methyl-β-cyclodextrin complex decreased MTT reduction, enhanced exocytosis of formazan, and promoted cell type-dependent increase in oxygen consumption. No cytotoxicity of cholesterol itself was revealed in trypan blue and propidium iodide assays.…”
Section: Conditioned Mediummentioning
confidence: 99%
“…Huang et al [22] reported that major contributions to tetrazolium salt reduction by common culture media such as albumin and fatty acids can obscure changes in the cell number during MTT and similar assays. Funk et al [13] found that reductive activity of human serum albumin produced concentration-dependent increase in the MTT signal, although it should be mentioned that such effect did not occur when bovine serum albumin was used.…”
Section: Discussionmentioning
confidence: 99%
“…One reason why MTT experiments were carried out in a culture medium lacking FBS was to minimise any interference from FBS components such as albumin (41). Even though we did not assess the effects of EB-1 on extracellular redox, Schroterova et al (42) found that MTT assays provide a reliable measure of cell viability in colon cancer cells exposed to diverse selenium-containing compounds at concentrations up to 256 μmol L -1 .…”
Section: Discussionmentioning
confidence: 99%